Kegebi Ik Tip Taybi Ka: histórias dos antepassados até o presente da Aldeia Muricizal à missão São Francisco - MUNDURUKU, Luiz Akay (2024)
This Final Paper (TCC) is the result of the construction of an Action Plan for teaching our history, prepared by me with the Missão São Francisco do Rio Cururu community, in Alto Tapajós. The work was prepared based on the summary of the research carried out during the course during the Community Time periods with the children of the founders of the village and that was how I was able to prepare the conclusion of my TCC. Learn about the history and narratives of our ancestors and the history of the founding of Aldeia Missão Francisco before the creation of Aldeia Muricizal. I tried to highlight the history of our ancestors and the history of the founding of the village, map, location, cartography, the narratives of our people and the photographic record of our ancestors and today, where they lived before, who their God is, who is the oldest draftsman in history who left the drawings in the sacred places where they walked before the arrival of the Portuguese, who are the head hunters, creation of the general assembly of the Munduruku people, for which they founded the association and social organization, arrival of Jesuits, productive activities of the community.